Career choices of the first year students of Madha Medical College - Raja, Ashrof; Jahnavi, G.; Patra, Satya Ranjan (International Journal Of Community Medicine And Public Health, 2017)
Background: It is not very clear about the factors that influence the career choices of the undergraduate medical students. Experiences in the college during their curriculum are the strong determinants in developing an attitude to different subjects and attitude plays a very important role in choosing the speciality. This study is sought to find out the career choices of the first year medical students and what influenced them to take up that particular career Methods: A cross sectional questionnaire based study was conducted in the first semester students of the Madha Medical College. The questionnaire was designed to find out the first choice of speciality, awareness of various subjects taught in a medical college, location preferences, and reasons influencing the preference, education level and occupation of their parents. Results: Out of a total of 150 students 141 (94%) were present on that day who had completed the questionnaire successfully. The mean age of the students was 17.8±0.6 (min=17, max=20). About 54% of the students were females and the rest 46% were males. The students belonging to urban area were 67% and that of rural area were 33%. The reasons quoted by the students for joining the MBBS course were personal interest 82%, parent’s interest 18%. None of the students could correctly answer the number of subjects taught in a medical college during the course. About half of the students did not know the duration of a specialization course after MBBS. The students interested to do specialization were 97% and interested to do IAS, or IPS were 2%. The most preferred career choices among the students were clinical subjects (71%), of which General Medicine and obstetrics & gynecology topped the list, followed by surgery and paediatrics; 24% chose pre-clinical subjects and anatomy was the most favoured, followed by physiology and the least preferred was biochemistry; only 2% were interested in paraclinical subjects of which community medicine, pharmacology and forensic medicine shared equal status but none of them wanted to specialize in pathology and microbiology. Personal interest was rated among 81% of the students in influencing their choice of speciality. After completion of education about 45% of the students wanted to settle in urban area and equal percentage of students in rural area. The students who wanted to settle in India after specialization was 87%, who wanted to go abroad were 7%. About 46% of the students wanted to join the corporate set up after specialization, 36% wanted to become private practitioners. About 46% of the students felt that 1 year is adequate for basic sciences. Conclusion: The career choices among the students of our institution were biased among the clinical subjects. The choices may change during the course of time which would be followed up. The role modelling by the faculty could be a factor in influencing their choices.